Stress Doppler Echocardiography in Systemic Sclerosis: Evidence for a Role in the Prediction of Pulmonary Hypertension. Issue 9 (26th August 2013) - Codullo, Veronica; Caporali, Roberto; Cuomo, Giovanna; Ghio, Stefano; D'Alto, Michele; Fusetti, Chiara; Borgogno, Elena; Montecucco, Carlomaurizio; Valentini, Gabriele
Abstract : Objective: Patients with systemic sclerosis (SSc) in whom pulmonary hypertension (PH) is not suspected have been reported to develop an inappropriate increase of pulmonary artery systolic pressure as estimated by Doppler echocardiography under conditions of exercise (pulmonary artery systolic pressure under exercise). We undertook this study to investigate whether this increase or any other parameter detectable by stress Doppler echocardiography has utility in predicting the development of PH in SSc. Methods: We enrolled a total of 170 patients with SSc previously investigated using standard and stress Doppler echocardiography and tissue Doppler imaging. Each patient was evaluated at baseline and yearly for skin and internal organ involvement. Right‐sided heart catheterization was carried out when PH was suspected. The baseline Cochin Risk Prediction Score was calculated retrospectively. Results: During followup, 6 patients (3.5%) developed PH. Compared with patients without any feature suggesting PH, the Cochin Risk Prediction Score was higher in this group (mean ± SD 4.2 ± 0.9 versus 3.4 ± 0.9; P < 0.05), as was the difference between pulmonary artery systolic pressure under exercise and pulmonary artery systolic pressure (Δpulmonary artery systolic pressure) (18.2 ± 7 mm Hg versus 9.4 ± 6.5 mm Hg; P < 0.001), even when adjusted for cardiac index changes. In multivariate analysis, Δpulmonary artery systolic pressure (hazard ratio [HR] 3.4 [95% confidence interval 1.4–8], P < 0.01) and Cochin Risk Prediction Score within the fifth quintile of the values registered in our series (HR 9.3 [95% confidence interval 1.4–63.7], P < 0.05) were the only factors independently predictive of PH during followup. A Δpulmonary artery systolic pressure cutoff of >18 mm Hg, identified by receiver operating characteristic curve analysis, had a sensitivity of 50% and a specificity of 90% for the development of PH during followup. Conclusion: An inappropriate response to exercise among patients with SSC is detectable by stress Doppler echocardiography. Independently of other clinical associations, increased Δpulmonary artery systolic pressure heralds PH. Stress Doppler echocardiography may represent an additional screening tool for this severe complication.